FEMINITAS DAN MAKEUP PADA ANIMASI NUSSA RARRA EPISODE: GIRLS TALK - Yosieana Duli Deslima (Jurnal Dakwah Tabligh, 2020)
This study aims to describe the form of the meaning of femininity contained in the animation "Nussa Rarra Episode Girls Talk". This study uses descriptive qualitative analysis with Charles Sanders Pierce's semiotics analysis. The results showed that in the animation Nussa Rarra episode Grils Talk represented the femininity of women. Women are familiar with make-up. It also shows the feminine side of women, which is gentle. Where femininity is trusted by women, it must be gentle, patient, kind, polite, beautiful, etc. Indonesian women are never out of talking about make-up. To look beautiful always follow the beauty trends from abroad, which gave rise to the Make-up Tutorial trend. Indonesian women lack confidence in their natural beauty and must put makeup on to look beautiful. Scenes of giving a makeup message in Islam are permissible but not permitted is to tabarruj. However, this animation seems to force that women do not have to put make up the slightest item to look beautiful because natural beauty is better than makeup and dress up.